Epidemiology of human Monkey-pox cases in Rivers State, Nigeria January 2017-June 2022 - Onu, Hastings Chinedu; Golden, Owhonda; Wali, I. Aaron; Adedire, B. Elizabeth; Balogun, Muhammed; Chidinma, Eze; Ayo, S. Adebowale; Emmanuel, Okolocha (Frontiers in Public Health, 2023)
The resurgence in monkey pox disease has posed a global health threat. Nigeria recorded increased number of reported monkey pox cases in 2017, with cases occurring in subsequent years. Notably, cases of monkey pox had been reported in western countries from an epidemiologically linked traveler with a travel history to Nigeria. The highest burden of cases of monkey pox is recorded in River state, Nigeria. Consequently, there is the need to examine the epidemiology of monkey pox according to time, place, person and geography in Rivers state. A retrospective analysis of monkey pox cases was conducted based on the data obtained from the Rivers State Disease Surveillance and Notification unit from January 2017- June 2022. A total of 112 suspected cases were reported during this period of which 49 (44%) were confirmed by laboratory diagnosis. Obio-Akpor (29) and Port Harcourt (9) Local Government Areas which make up the urban centers of the state recorded most cases of monkey pox. More males (36) were affected than females (10), and the age group mostly affected was from 20-29 years, however increased cases of monkey pox was found in the months of September to November in most of the years reviewed. Monkey pox is prevalent in Rivers state, although the pattern follows a declining trend. Therefore, the state government should put appropriate mechanisms in place to eradicate the disease